2013
DOI: 10.2478/pjvs-2013-0104
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of dogs with lymphocyte proliferative responses to food allergens in canine allergic dermatitis

Abstract: The aim of the present study was to examine the correlation between the results of lymphocyte proliferative test (LPT) specific to food allergens and allergic skin diseases in dogs. Investigations were performed in 138 dogs with allergic skin diseases diagnosed in a private animal hospital. Of the 138 animals, 97 cases had positive reactions in LPT specific to food allergens. Of these 97 dogs, 67 animals were diagnosed with canine atopic dermatitis (CAD), but 30 dogs did not have IgE antibodies to environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 6 publications
1
22
0
1
Order By: Relevance
“…Previous studies have shown that ALD constitutes 14 to 25% of CAD, which is similar to that of intrinsic AD in humans (20%) (Tokura 2010, Fujimura 2011, Kabashima et al 2013, Kawano et al 2013, Suto et al 2014. From what we know of the mode of action of CsA, it may be more effective against intrinsic AD, because IL-2 is a Th1 related cytokine and intrinsic AD in humans is Th1-dominant.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have shown that ALD constitutes 14 to 25% of CAD, which is similar to that of intrinsic AD in humans (20%) (Tokura 2010, Fujimura 2011, Kabashima et al 2013, Kawano et al 2013, Suto et al 2014. From what we know of the mode of action of CsA, it may be more effective against intrinsic AD, because IL-2 is a Th1 related cytokine and intrinsic AD in humans is Th1-dominant.…”
Section: Discussionmentioning
confidence: 81%
“…The PBMC's utilized in this study were sent by veterinarians for a previously described standard lymphocyte proliferation assay [5,12,25], and after the assay was completed, the remaining cells were used to examine T-lymphocyte responses to the hydrolyzed diets. Therefore, we did not have access to the history and clinical features of the dogs and blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…Another report evaluating clinical cases of dogs with chronic dermatitis and suspected food hypersensitivity confirmed this trend [5]. In addition, a study conducted on dogs with gastrointestinal symptoms clinically diagnosed as inflammatory bowel disease, found peripheral lymphocytes reactive to at least one food antigen in all the animals [12]. Flow cytometry analysis revealed that the type IV lymphocytes associated with hypersensitivity were CD4 + helper T-lymphocytes [5,21].…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Ryota Asahina 1) , Takafumi Osumi 2) , Takuya Mizuno 3) , Yuri Oshima 4) , Michiyo Kadoya 5) , Tae Murai 6) , Kentaro Yamagishi 7) , Koji Nishifuji 2) , Masahiko Nagata 8) , Sadatoshi…”
unclassified